Needs of fisherfolk and bio-diversity conservation - Ojha, S N; Goswami, Mukunda; Salim, Shyam S; Ayyappan, S (Indian Journal of Fisheries, 2011)
A survey of 400 fisherfolk in 8 coastal villages of the selected 4 maritime states ofIndia revealed that roots of problems offisherfolks center around the present methods of urbanization and industrialization, techno-social advancements of fishers and developmental intervention process. These have resulted into unemployment and other social problems and even unrests. The solution to these problems is perceived to come in two phases. In phase one, developmental interventions, income diversification and infrastructure development needs to be strengthened to reduce the cost of fishing and increase the income per catch. Thereafter the measures like implementation of code of conducts for responsible fisheries needs to be implemented to estimate the biodiversity process. This entire social process is depicted in the paper as a Social Model for the Conservation of Coastal BiD-diversity (SOMCOCOBID).